The Impact of Lifetime Events on Pensions : NDC Schemes in Poland, Italy, and Sweden and the Point Scheme in Germany - Chłon-Dominczak, Agnieszka; Góra, Marek; Kotowska, Irena E.; Magda, Iga; Ruzik-Sierdzinska, Anna; Strzelecki, Paweł (World Bank, Washington, DC, 2019)
The paper focuses on the interrupted careers in four countries where pensions are based on lifetime labor income, but they have different labor market patterns. High levels of employment in Germany and Sweden are in contrast with low levels of employment, particularly for women, in Italy and Poland. Career interruptions of women in Italy mean early withdrawal from the labor market, while in Sweden women choose part-time employment. Lower employment rates and gender pay gaps are important causes of differences in expected pension levels. The pension system design and demographics are also different. Prolonging working lives and reducing gender gaps in employment and pay, particularly for those at risk of interrupted careers, is key to ensure decent old-age pensions